The fundamentals of product design - Morris, Richard D., 1962- (Lausanne ; Worthing : AVA Academia, 2009)
Understand the process of product design, from start to finish * Detailed overview, perfect introduction for students * More than 200 color images plus easy-to-understand flow charts What is product design? It's materials, manufacturing, ideas, CAD, engineering, art, marketing, and so much more. The Fundamentals of Product Design is an integrated overview of the design process, gathering information about every facet from idea to execution to selling into one handy volume. Full of inspiring visuals and enlightening diagrams, this book is a celebration of everyday design and a remarkable one-volume reference work for students and working designers.
Includes bibliographical references.
Keywords: Design, Industrial; Manufactures -- Design